Evaluation of fruit tree waterstress condition and transpiration with heat fl ux sensors - Nagy, A.; Riczu, P.; Tamás, J.; Szabó, Z.; Soltész, M.; Nyéki, J. (International Journal of Horticultural Science, 2016)
In this study the transpiration properties and response to heat stress of Granny Smith and Jonagold apple species were measured. The examinations were set at an orchard near to Debrecen. The chosen trees were two years old, without fruits, in 20l container, placed in the mixture of mulch matrix, wood chips and sawdust and grown at the same climatic conditions. One of the most important goals was to determine the leaf area of the trees which is a basic data for transpiration modeling. Leaf area was larger (signifi cance level p